The Effect of Ball Feeling Variation Training on Dribbling Skills In Futsal Extracurricular Members of Senior High School 1 Jalancagak - Mohammad Sya’ban Fadhillah; Abdul Salam Hidayat; Abdulloh Abdulloh (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2022)
This study aims to determine the effect of ball feeling variations on dribbling skills in futsal extracurricular members of SMA Negeri 1 Jalancagak. This study uses a quantitative approach. When viewed from the type of data presented, this type of research is an experiment with a "One Group Pretest-Posttest Design" design. The research population was participants who took part in futsal extracurricular at SMA Negeri 1 Jalancagak, totalling 20 students. The instrument used to measure dribbling skills is a modified dribbling test by Subagyo Irinto (1995), which was tested by Dica Febri Wardana (2015) with a validity test of 0.710 and a reliability test of 0.703. The data analysis technique used prerequisite tests, namely the Kolmogorov-Smirnov test for normality test, homogeneity test and t-test for hypothesis testing at a significant level of 5%. The results showed that there was a significant effect of ball feeling training on increasing dribbling skills in participants who took part in futsal extracurricular activities, with the results obtained from the pretest mean of 20.5725 and Standard Deviation of 1.71941, while for the posttest the mean value of 19.2270 with Standard Deviation of 1.42408. Judging from these results, it can be seen that the increase before and after students was given treatment using the ball feeling variation exercise method was an increase of 15.29%.